Anticorrosion strategy for magnesium alloys through a superhydrophobic approach utilizing slippery liquid-infused porous surface coating - Muhammad Hafizuddin, Alias; Juliawati, Alias; Nasrul Azuan, Alang (Springer Nature, 2024)
Magnesium (Mg) and its alloys have a wide range of possible uses in various industries because of their lightweight properties. Nevertheless, the practical applications of Mg alloys are significantly limited due to their restricted corrosion resistance, despite their numerous desirable properties including low density, high specific strength, and excellent biocompatibility. Applying a protective coating to the surface can effectively inhibit corrosion. In order to create slippery liquid-infused porous surfaces (SLIPS), it is necessary to have suitable porous micro/nanostructures and infuse liquid lubricant using surface treatment. The coatings on Mg alloys must significantly enhance the properties such as hardness, adhesion, wear and scratch resistance, elastic modulus, tensile and fatigue strength, impact resistance, and friction coefficient, while providing superior corrosion resistance. This method has been shown to effectively resist corrosion in Mg alloys. This review article provides an overview of recent formulation of SLIPS to enhance the water-repellent properties of Mg alloys for corrosion prevention. The SLIPS technique on Mg alloys and its functional corrosion performance by biomimetic-based SLIPS, polymer-based, and layered double hydroxide (LDH) techniques breakthroughs are disclosed. SLIPS has the potential to expand the range of applications for Mg alloys, including self-cleaning, anti-icing, drag reduction, and anti-fouling capabilities.